The Impact of Transactional Leadership, Affective Commitment, and Job Satisfaction on In-Role Employee Behavior - Putri, Denada; Hilmy, Irfan Aziz; Adrian, Renno; Iqbal, Shaif; Mukhibulloh, (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
This study aims to examine the impact of transactional leadership, job satisfaction, and affective commitment on employees’ in-role behavior at PT Wijaya Gyokai Indonesia. A quantitative research design was employed, utilizing a survey method involving 60 respondents selected through simple random sampling. Data were gathered using a structured questionnaire with a 5-point Likert scale and analyzed using multiple linear regression. The t-test was used to evaluate the partial effects of each variable, while the F-test assessed the overall model significance. The findings reveal that, individually, transactional leadership (t = 7.195; p < 0.001), affective commitment (t = 7.160; p < 0.001), and job satisfaction (t = 6.168; p < 0.001) all exert a positive and significant influence on employees’ in-role behavior. Simultaneously, the three variables significantly affect in[1]role behavior (F = 43.714; p < 0.001), explaining 68.5% of the variance, with the remaining 31.5% attributed to factors outside the model. These results highlight the critical role of transactional leadership, affective commitment, and job satisfaction in promoting positive employee behavior within the organization. Practically, this suggests that companies should implement initiatives that enhance these factors—such as well-designed reward systems, transparent career development opportunities, and programs that foster employee engagement—to improve overall organizational performance.